Characterization and Application of Zinc Oxide Nanoparticles - Amrullah, Nidaa Yousif; Abdullah, Rand Sabry; Hazbar, Abdullah Muhsin (Journal of Science in Medicine and Life, 2025)
Zinc oxide nanoparticles (ZnO-NPs) have garnered significant interest in the food and agricultural sectors for their potential to eliminate or reduce microbial activity. The antibacterial properties of ZnO nanoparticles may improve food quality, hence directly impacting human health. ZnO-NPs, among the most extensively studied inorganic nanoparticles, have been used across several domains and has the potential to rapidly garner attention in the food and agricultural sectors. This study covers the synthesis of ZnO nanoparticles, their characterisation, modifications, uses, antimicrobial efficacy, testing methodologies, and effects, covering both bactericidal and bacteriostatic processes. This study aims to enhance understanding of the preparation and use of ZnO nanoparticles in the food and agricultural sectors, while also promoting their advancement in these domains.